Retinal degeneration protein 3 controls membrane guanylate cyclase activities in brain tissue - Chen, Yaoyu; Bräuer, Anja U.; Koch, Karl-Wilhelm (Frontiers in Molecular Neuroscience, 2022)
The retinal degeneration protein RD3 is involved in regulatory processes of photoreceptor cells. Among its main functions is the inhibition of photoreceptor specific membrane guanylate cyclases during trafficking from the inner segment to their final destination in the outer segment. However, any physiological role of RD3 in non-retinal tissue is unsolved at present and specific protein targets outside of retinal tissue have not been identified so far. The family of membrane bound guanylate cyclases share a high homology of their amino acid sequences in their cytoplasmic domains. Therefore, we reasoned that membrane guanylate cyclases that are activated by natriuretic peptides are also regulated by RD3. We analyzed transcript levels of the rd3 gene and natriuretic peptide receptor genes Npr1 and Npr2 in the mouse retina, cerebellum, hippocampus, neocortex, and the olfactory bulb during development from the embryonic to the postnatal stage at P60. The rd3 gene showed a lower expression level than Npr1 and Npr2 (encoding for GC-A and GC-B, respectively) in all tested brain tissues, but was at least one order of magnitude higher in the retina. RD3 and natriuretic peptide receptor GCs co-express in the retina and brain tissue leading to functional tests. We expressed GC-A and GC-B in HEK293T cells and measured the inhibition of GCs by RD3 after activation by natriuretic peptides yielding inhibitory constants around 25 nM. Furthermore, endogenous GCs in astrocytes were inhibited by RD3 to a similar extent. We here show for the first time that RD3 can inhibit two hormone-stimulated GCs, namely GC-A and GC-B indicating a new regulatory feature of these hormone receptors.